2022
DOI: 10.1371/journal.pbio.3001591
|View full text |Cite
|
Sign up to set email alerts
|

Cortical asymmetries at different spatial hierarchies relate to phonological processing ability

Abstract: The ability to map speech sounds to corresponding letters is critical for establishing proficient reading. People vary in this phonological processing ability, which has been hypothesized to result from variation in hemispheric asymmetries within brain regions that support language. A cerebral lateralization hypothesis predicts that more asymmetric brain structures facilitate the development of foundational reading skills like phonological processing. That is, structural asymmetries are predicted to linearly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…neurochemical makeup (Zilles & Amunts, 2018). However, there is still reason to explore the structural contribution of BA47 to reading ability as this region is involved in multiple reading processing (e.g., accessing semantics [Dickens et al, 2019], covert articulation [Hope et al, 2014], semantics articulation [Eckert et al, 2022], just to name a few). For example, Sabb et al (2007) explored the role of BA47 in working memory and found increased activity in the pars orbitalis for primed compared to unprimed items.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…neurochemical makeup (Zilles & Amunts, 2018). However, there is still reason to explore the structural contribution of BA47 to reading ability as this region is involved in multiple reading processing (e.g., accessing semantics [Dickens et al, 2019], covert articulation [Hope et al, 2014], semantics articulation [Eckert et al, 2022], just to name a few). For example, Sabb et al (2007) explored the role of BA47 in working memory and found increased activity in the pars orbitalis for primed compared to unprimed items.…”
Section: Significancementioning
confidence: 99%
“…This region appears to be most distinct from BA45 and BA44, whereby BA47 has quite a different structural and neurochemical makeup (Zilles & Amunts, 2018). However, there is still reason to explore the structural contribution of BA47 to reading ability as this region is involved in multiple reading processing (e.g., accessing semantics [Dickens et al., 2019], covert articulation [Hope et al., 2014], semantics articulation [Eckert et al., 2022], just to name a few). For example, Sabb et al.…”
Section: Introductionmentioning
confidence: 99%
“…In the dyslexia literature, abnormalities in brain asymmetry in both cortical gray matter and white matter tracts from the language network have been documented, in both case studies/reviews (Galaburda et al, 1985 ; Geschwind and Galaburda, 1985 ; Leonard and Eckert, 2008 ); and cross-sectional research on dyslexia (see Duara et al, 1991 ; Niogi and McCandliss, 2006 ; Altarelli et al, 2014 ; Zhao et al, 2016 ; and Banfi et al, 2019 ). A recent large-scale cross-sectional study on both adults and children reported more modest effect sizes for asymmetry differences in cortical regions that are associated with phonological processing (Eckert et al, 2022 ). Correspondingly, one might expect there to be clear differences in cerebral asymmetry of cortical oscillations between typical and poor readers.…”
Section: Entrainment Across Different Frequency Bandsmentioning
confidence: 99%
“…The question of whether an impairment is a cause of DD or whether it is merely an accompanying deficit with no causal significance is also fundamental to the assessment of neural dysfunctions that may occur together with impaired abilities such as dyslexia [ 161 , 162 ]. Theories regarding the neural basis of DD mainly rely on functional magnetic resonance imaging (fMRI) studies [ 125 , 126 , 127 , 128 , 129 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 ]. An increase in the blood-oxygen-level-dependent (BOLD) signal in an area of the brain shows that this area is receiving sensory afferents or input from other brain areas [ 191 , 192 ].…”
Section: What Functional Mri and Cerebral Lesions Reveal About The Ne...mentioning
confidence: 99%